MAKLUMAT INDUSTRI DAN SAINS INFORMATION SERVICE FOR COMMERCE & INDUSTRY - Perpustakaan, Universiti Sains Malaysia (Perpustakaan Universiti Sains Malaysia, 2003)
The Malaysia External Trade Development Corporation (MATRADE) is intensifying the promotion of Malaysian products and services in existing as well as in new and emerging markets, sources were quoted. MATRADE would be expanding the number and scope of its promotional activities which will be covering all regions with special emphasis given to China, West Asia and Asean this year.